Better on toast : happiness on a slice of bread : 70 irresistible recipes - Donenfeld, Jill (William Morrow an imprint of HarperCollinsPublishers, 2015)
"Better on Toast features delicious, quick, easy-to-follow recipes for toasts with every possible topping-- from hot to cold and savory to sweet. Anyone can make delicious toasts, no matter his or her level of experience or kitchen size. Whether you use thick-cut French bread, slices of whole wheat, or her gluten-free bread recipe, Jill puts emphasis on flavor, using quality, wholesome ingredients to make each recipe stand out"--Excerpt from Amazon.com.